MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN TEKS CERITA ANAK MELALUI METODE SURVEY, QUESTION, READ, RECITE, REVIEW (SQ3R) DI KELAS V SDN 2 SUNTENJAYA KABUPATEN BANDUNG BARAT - Noortiany, Sarah (2014)
This research was done to observe the low reading-understanding ability of the students of the 5th grade of SDN 2 Suntenjaya, especially in Bahasa Indonesia. It was shown in their under average achievement in KKM (Kriteria Ketuntasan Minimum). It was caused by the methods and strategies applied by the teachers were found to be not-so-appropriate and unattractive for the students. Hence, this research was focused on improving the reading-understanding ability on children's narrative story using SQ3R method. The objective of the research was to know and describe the data that were gathered during the implementation of using SQ3R method on the 5th graders of SDN 2 Suntenjaya with the goal to improve their reading-understanding ability and the result of the implementation of the method. The research were done using the Classroom Action Research method that was consisted of four main steps; planning, realization, observation and reflective action. The research were done in two cycles to the 5th graders of SDN 2 Suntenjaya with the population of 30 students. The result of the research showed that SQ3R method was proven to give positive outcome on improving the student's reading-understanding ability score. It was shown from the result of the reading-understanding ability test score in the 1st cycle that reached an average of 72,7 points and raised to the average of 80,2 points in the 2nd cycle with the completeness study that reached the average percentage of 78% in the 1st cycle and raised to average percentage of 93% in the 2nd cycle. From these results, we can conclude that SQ3R method was proven to improve the student's reading-understanding ability on children's narrative story. Hence, this method is hoped to be given a chance to be used as alternative method in teaching in classroom, either in Bahasa Indonesia or any other subjects that require the students to have reading-understanding ability.